2006
DOI: 10.1111/j.1556-4029.2006.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Hirschsprung's Disease Diagnosed During Forensic Autopsy

Abstract: We report a case of fatal Hirschsprung's disease (HD) discovered at autopsy. A 20-year-old man collapsed at home. Emergency medical personnel found him in cardiac arrest and all resuscitative efforts failed. He had a past history of chronic constipation since infancy. Forensic autopsy revealed a megacolon full of gas and stools. Microscopic examination showed absence of ganglion cells in a short segment of the rectum and enterocolitis in the left and transverse colon. HD is rarely described in adults. In many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
(36 reference statements)
1
6
0
1
Order By: Relevance
“…Because of the possibility of subclinical HAEC, Teitelbaum [27] suggested a histologic grading system for HAEC as a useful method for early detection of infants at risk. Hirschsprung's disease-associated enterocolitis remains a significant cause of morbidity and mortality in HSCR [3,7], which may even extend into the adult years [28]. It appears no less dangerous in its subclinical form, with Marty et al [1] reporting fatal postoperative enterocolitis in 5 children with fairly mild clinical symptoms 3 weeks to 20 months after uncomplicated HSCR surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the possibility of subclinical HAEC, Teitelbaum [27] suggested a histologic grading system for HAEC as a useful method for early detection of infants at risk. Hirschsprung's disease-associated enterocolitis remains a significant cause of morbidity and mortality in HSCR [3,7], which may even extend into the adult years [28]. It appears no less dangerous in its subclinical form, with Marty et al [1] reporting fatal postoperative enterocolitis in 5 children with fairly mild clinical symptoms 3 weeks to 20 months after uncomplicated HSCR surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports showed that IMC may develop devastating complication, such as perforation of the dilated bowel and subsequent peritonitis and sepsis, metabolic and electrolyte abnormalities. [14] Compression of the diaphragm by the megacolon with subsequent respiratory failure, [15] colonic volvulus, [11] compression of the pelvic veins and bladder outlet by the megacolon, with resulting acute shower thromboemboli in the lungs [4,13] also have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although mortality involves mainly newborns or young children, some reports described adult deaths due to septic complications secondary to severe enterocolitis [5]. Postoperative results of the surgical treatment of HSCR appear to be satisfactory.…”
Section: Introductionmentioning
confidence: 94%